A high entropy alloy self-lubricating material and titanium alloy composite component and its preparation method and application

By mixing the medium-entropy alloy, aluminum and silver and performing discharge plasma sintering, a high-entropy alloy self-lubricating material is obtained and solid-phase diffusion welding is performed with the titanium alloy, which solves the problem of brittle intermetallic compounds generated by titanium alloy and high-entropy alloy in heterogeneous welding, and achieves efficient metallurgical combination of heterogeneous connection and welding interface, and improves the wear resistance of titanium alloy.

CN115555561BActive Publication Date: 2025-04-18LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211382391.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2025-04-18
Estimated Expiration
2042-11-07

AI Technical Summary

Technical Problem

In the prior art, titanium alloys and high entropy alloys are prone to generate brittle intermetallic compounds during different welding, resulting in deterioration of joint performance, and no relevant reports have been reported in the welding research of HEA and titanium alloys.

Method used

By mixing the medium-entropy alloy, aluminum and silver and sintering the discharge plasma, a high-entropy alloy self-lubricating material is obtained, and then wrapped with the titanium alloy and undergo solid phase diffusion welding treatment to achieve metallurgical bonding between the different types of connection and the welding interface.

Benefits of technology

The heterogeneous connection between titanium alloy and high-entropy alloy is achieved, and a dense, defect-free welded joint is obtained, which improves the wear resistance of titanium alloy and the bonding strength of the welding interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115555561B_ABST
    Figure CN115555561B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of high entropy alloys, and in particular to a high entropy alloy self-lubricating material and titanium alloy composite component and its preparation method and application. The present invention performs solid phase diffusion welding under vacuum conditions to achieve heterogeneous connection between titanium alloy and high entropy alloy self-lubricating material, and obtains a weld interface that achieves metallurgical bonding, dense structure, and defect-free joints, giving full play to their respective advantages, reducing friction coefficients, and improving wear resistance of titanium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy alloys, and in particular to a high entropy alloy self-lubricating material and titanium alloy composite component, and a preparation method and application thereof. Background Art

[0002] Titanium and titanium alloys have been highly valued and widely used in the aerospace field due to their excellent comprehensive mechanical properties. However, their wear resistance is not strong, and their oxidation resistance decreases significantly with the increase of temperature, especially for wear-resistant parts such as aviation spherical bearings, where wear becomes their main failure form. High entropy alloys (HEA) exhibit properties superior to traditional metal materials, such as high strength, high wear resistance, and good radiation resistance, and have become a research frontier and hotspot in the alloy field in recent years. Composite components composed of titanium alloy / HEA dissimilar metals can combine the excellent properties of titanium alloy and HEA, so that the wear resistance of parts is improved on the basis of excellent mechanical properties.

[0003] At present, there are few studies on the weldability of HEA with dissimilar materials, mainly involving the dissimilar welding of mature HEA, such as CoCrFeMnNi and CoCrFeNiCu with stainless steel. Researchers from the University of Lisbon, Portugal (JPO Oliveira, Jiajia Shen, Z. Zeng, Jeong Min Park, Yeon Taek Choi, N. Schell, E. Maawad, N. Zhou, Hyoung Seop Kim, Dissimilar laser welding of a CoCrFeMnNi high entropy alloy to 316 stainless steel, Script Materialia, Volume 206, 2022, 114219) used laser welding technology to obtain defect-free joints of CoCrFeMnNi and 316 stainless steel. Li Juan et al. (Li Juan, Zhao Honglong, Zhou Nian, Zhang Yingzhe, Qin Qingdong, Su Xiangdong, Vacuum diffusion welding of CoCrFeNiCu high entropy alloy and 304 stainless steel, Acta Metallurgica Sinica, 2021, 57, 1567-1578) studied the vacuum diffusion welding of CoCrFeNiCu and 304 stainless steel. The results showed that the strength of the welded joint was higher than that of the parent material, and a high-quality connection could be achieved. Dissimilar welding related to titanium alloys is mainly concentrated in its connection with stainless steel, copper, etc., but in the process of dissimilar fusion welding, the mixing of the two substrates may promote the formation of harmful phases, especially with titanium alloys. During the fusion welding process, a large amount of brittle intermetallic compounds are easily generated, which deteriorates the performance of the joint. Therefore, effectively preventing the large-scale generation of intermetallic compounds is a difficulty in dissimilar welding, and there is no related report on the welding of HEA and titanium alloys. Summary of the invention

[0004] The object of the present invention is to provide a high entropy alloy self-lubricating material and titanium alloy composite component and its preparation method and application. The preparation method can realize heterogeneous connection between the high entropy alloy self-lubricating material and the titanium alloy, realize metallurgical bonding at the welding interface, and obtain a dense and defect-free welding joint.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a high entropy alloy self-lubricating material and a titanium alloy composite component, comprising the following steps:

[0007] After mixing medium entropy alloy, aluminum and silver, spark plasma sintering is performed to obtain high entropy alloy self-lubricating material;

[0008] After encapsulating the high entropy alloy self-lubricating material and the titanium alloy, solid phase diffusion welding is performed to obtain the high entropy alloy self-lubricating material and titanium alloy composite component;

[0009] The process of the solid phase diffusion welding treatment is: raising the pressure to 10MPa at room temperature, raising the temperature to 600-750°C at a heating rate of 10-30°C / min, keeping the temperature for 5-15min, continuing to raise the pressure to 30-40MPa, raising the temperature to 700-900°C for the second time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 15-30min, raising the pressure to 80-110MPa, raising the temperature to 1000-1200°C for the third time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 3-7h, and air cooling.

[0010] Preferably, the mass ratio of the medium-entropy alloy, aluminum and silver is (75-85):(5-15):(5-15).

[0011] Preferably, the medium entropy alloy is a CoCrNiFe high entropy alloy;

[0012] The titanium alloy is TC4 titanium alloy.

[0013] Preferably, the particle size of the medium entropy alloy is 10 to 50 μm.

[0014] Preferably, the particle size of the aluminum is 10 to 50 μm;

[0015] The particle size of the silver is 15 to 35 μm.

[0016] Preferably, the spark plasma sintering process is: under a pressure of 20 to 40 MPa, the temperature is raised from room temperature to 700 to 1000° C. at a heating rate of 8 to 10° C. / min, and the molding is performed for 10 to 20 minutes.

[0017] Preferably, the spark plasma sintering process is: under a pressure of 25 to 35 MPa, the temperature is raised from room temperature to 900 to 1000° C. at a heating rate of 8 to 10° C. / min, and the molding is performed for 15 to 20 minutes.

[0018] Preferably, the process of the solid phase diffusion welding treatment is: raising the pressure to 10MPa at room temperature, raising the temperature to 600-700°C at a heating rate of 15-25°C / min, keeping warm for 8-12min, continuing to raise the pressure to 35-40MPa, raising the temperature to 700-800°C for the second time at a heating rate of 8-10°C / min, keeping warm and pressurizing for 20-30min, raising the pressure to 100-110MPa, raising the temperature to 1050-1100°C for the third time at a heating rate of 8-10°C / min, keeping warm and pressurizing for 5-6h, and air cooling.

[0019] The present invention also provides a high entropy alloy self-lubricating material and titanium alloy composite component prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides the use of the high entropy alloy self-lubricating material and titanium alloy composite component described in the above technical solution in the preparation of high-strength, toughness and wear-resistant parts.

[0021] The invention provides a preparation method of a high entropy alloy self-lubricating material and a titanium alloy composite component. The method comprises the following steps: mixing a medium entropy alloy, aluminum and silver, and then performing spark plasma sintering to obtain a high entropy alloy self-lubricating material; sheathing the high entropy alloy self-lubricating material and the titanium alloy, and then performing solid phase diffusion welding treatment under vacuum conditions to obtain the high entropy alloy self-lubricating material and the titanium alloy composite component; the solid phase diffusion welding treatment process comprises: increasing the pressure to 10MPa at room temperature, increasing the temperature to 600-750°C at a heating rate of 10-30°C / min, keeping the temperature for 5-15min, continuously increasing the pressure to 30-40MPa, heating the temperature to 700-900°C for the second time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 15-30min, increasing the pressure to 80-110MPa, heating the temperature to 1000-1200°C for the third time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 3-7h, and air cooling. The present invention performs solid phase diffusion welding to initially establish physical contact between the titanium alloy and the high entropy alloy self-lubricating material, and then causes plastic deformation of the surface through yield and creep mechanisms under the action of high temperature and external pressure, and the contact area of ​​the surface gradually increases, and the atoms on the contact surface diffuse with each other to form a tight bond. Due to the deformation causing defects such as lattice distortion, dislocation, and vacancy, the interface atoms are in a highly activated state, the tissue composition is gradually homogenized, the original interface disappears, and heterogeneous connection is achieved, so that the welding interface achieves metallurgical bonding, dense tissue, and a defect-free joint, which gives full play to their respective advantages, can reduce the friction coefficient, and improve the wear resistance of the titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the HEA / TC4 self-lubricating composite material described in Example 1;

[0023] Figure 2 This is the SEM image of the HEA / TC4 self-lubricating composite material described in Comparative Example 2. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a high entropy alloy self-lubricating material and a titanium alloy composite component, comprising the following steps:

[0025] After mixing medium entropy alloy, aluminum and silver, spark plasma sintering is performed to obtain high entropy alloy self-lubricating material;

[0026] After encapsulating the high entropy alloy self-lubricating material and the titanium alloy, solid phase diffusion welding is performed to obtain the high entropy alloy self-lubricating material and titanium alloy composite component;

[0027] The process of the solid phase diffusion welding treatment is: raising the pressure to 10MPa at room temperature, raising the temperature to 600-750°C at a heating rate of 10-30°C / min, keeping the temperature for 5-15min, continuing to raise the pressure to 30-40MPa, raising the temperature to 700-900°C for the second time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 15-30min, raising the pressure to 80-110MPa, raising the temperature to 1000-1200°C for the third time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 3-7h, and air cooling.

[0028] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0029] The invention mixes a medium entropy alloy, aluminum and silver, and then performs spark plasma sintering to obtain a high entropy alloy self-lubricating material.

[0030] In the present invention, the medium entropy alloy is preferably a CoCrNiFe-based high entropy alloy, and the CoCrNiFe-based high entropy alloy is preferably an equiatomic ratio CoCrNiFe alloy; the particle size of the high entropy alloy is preferably 10 to 50 μm.

[0031] In the present invention, the particle size of the aluminum is preferably 10 to 50 μm.

[0032] In the present invention, the particle size of the silver is preferably 15 to 35 μm.

[0033] In the present invention, the mass ratio of the high entropy alloy, aluminum and silver is preferably (75-85):(5-15):(5-15), and more preferably (78-82):(8-12):(8-12).

[0034] In the present invention, the silver serves as a solid lubricant, and the aluminum serves as a solid lubricant to prepare Al2O3 alloys with different Al contents from CoCrNiFe. x CoCrNiFe quinary high entropy alloy.

[0035] In the present invention, the mixing method is preferably ball milling. The present invention does not have any special limitation on the ball milling process. It can be carried out by a process well known to those skilled in the art and ensure that the high entropy alloy, aluminum and silver are mixed evenly.

[0036] In the present invention, the spark plasma sintering process is preferably: under a pressure of 20 to 40 MPa, the temperature is increased from room temperature to 700 to 1000°C at a heating rate of 8 to 10°C / min, and the molding is performed for 10 to 20 minutes; more preferably, under a pressure of 25 to 35 MPa, the temperature is increased from room temperature to 900 to 1000°C at a heating rate of 8 to 10°C / min, and the molding is performed for 15 to 20 minutes.

[0037] In the present invention, the spark plasma sintering is preferably performed by placing the mixed mixture in a graphite mold for spark plasma sintering.

[0038] In the present invention, the spark plasma sintering is used to achieve Al x Preparation of CoCrNiFe based high entropy alloy self-lubricating composites.

[0039] After the spark plasma sintering is completed, the present invention further includes cooling and demolding in sequence; the present invention has no special limitation on the cooling process, and a process well known to those skilled in the art can be used to cool the temperature to room temperature; the present invention has no special limitation on the demolding process, and a process well known to those skilled in the art can be used.

[0040] After obtaining the high entropy alloy self-lubricating material, the present invention sheathes the high entropy alloy self-lubricating material and the titanium alloy, and then performs solid phase diffusion welding to obtain the high entropy alloy self-lubricating material and titanium alloy composite component.

[0041] In the present invention, the titanium alloy is preferably TC4 titanium alloy, and the chemical composition of the TC4 titanium alloy is preferably Ti6Al4V.

[0042] Before sheathing, the present invention preferably pre-treats the high entropy alloy self-lubricating material and the titanium alloy respectively, and the pre-treatment preferably includes grinding and polishing performed in sequence; the present invention does not have any special limitation on the grinding and polishing process, and the process familiar to those skilled in the art can be used.

[0043] In the present invention, the encapsulation process is preferably to place the high entropy alloy self-lubricating material and the titanium alloy in a carbon steel encapsulation, evacuate, and perform vacuum packaging to obtain an encapsulation for hot isostatic pressing. The present invention does not have any special limitation on the evacuation process, and a process well known to those skilled in the art can be used.

[0044] After obtaining the sheath for hot isostatic pressing, the present invention also preferably includes sandblasting the obtained sheath. The present invention does not have any special limitation on the process of sandblasting, and the process well known to those skilled in the art can be used. In the present invention, the purpose of sandblasting is to remove oil stains on the surface of the sheath so as to pollute the furnace chamber of the equipment furnace.

[0045] In the present invention, the process of the solid phase diffusion welding treatment is: raising the pressure to 10MPa at room temperature, raising the temperature to 600-750°C at a heating rate of 10-30°C / min, keeping the temperature for 5-15min, continuing to raise the pressure to 30-40MPa, raising the temperature to 700-900°C at a heating rate of 8-10°C / min for the second time, keeping the temperature and pressure for 15-30min, raising the pressure to 80-110MPa, raising the temperature to 1000-1200°C at a heating rate of 8-10°C / min for the third time, keeping the temperature and pressure for 15-30min, Preferably, the pressure is increased to 10MPa at room temperature, increased to 600-700°C at a heating rate of 15-25°C / min, kept warm for 8-12min, and then the pressure is increased to 35-40MPa, and the temperature is increased to 700-800°C for the second time at a heating rate of 8-10°C / min, and the temperature is kept at this temperature for 20-30min. After the pressure is increased to 100-110MPa, the temperature is increased to 1050-1100°C for the third time at a heating rate of 8-10°C / min, and the temperature is kept at this temperature for 5-6h, and then air-cooled.

[0046] In the present invention, the solid phase diffusion welding process is preferably performed in a hot isostatic pressing device.

[0047] In the present invention, the effect of controlling the condition parameters of the solid phase diffusion welding process within the above-mentioned range is to make the high entropy alloy self-lubricating composite material and the titanium alloy dissimilar interface contact each other seamlessly, and almost no obvious plastic deformation and oxidation will occur at the metal joint. After applying pressure, the contact area increases, which greatly promotes the diffusion flow of atoms at high temperature, thereby realizing a weld with excellent properties and strength.

[0048] The present invention also provides a high entropy alloy self-lubricating material and titanium alloy composite component prepared by the preparation method described in the above technical solution.

[0049] The present invention also provides the use of the high entropy alloy self-lubricating material and titanium alloy composite component described in the above technical solution in the preparation of high-toughness and wear-resistant parts. The high-toughness and wear-resistant parts are preferably used in the aerospace field or the medical and livelihood field. The present invention does not have any special restrictions on the method of the application, and the method well known to those skilled in the art can be used.

[0050] The high entropy alloy self-lubricating material and titanium alloy composite component provided by the present invention, as well as the preparation method and application thereof are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0051] Example 1

[0052] 80 parts by weight of high entropy alloy powder (the composition of the high entropy alloy is CoCrNiFe, and the particle size is 20 μm), 8 parts by weight of aluminum powder (the particle size is 30 μm) and 12 parts by weight of silver powder (the particle size is 15 μm) are ball-milled and mixed until uniformly mixed, and then spark plasma sintered in a graphite mold (the process of spark plasma sintering is: under a pressure of 30 MPa, the temperature is increased from room temperature to 950° C. at a rate of 10° C. / min, and molded for 20 minutes), then cooled to room temperature, and demolded to obtain a high entropy alloy self-lubricating composite material;

[0053] Grinding and polishing the TC4 titanium alloy and the high entropy alloy self-lubricating composite material respectively to obtain the pretreated TC4 titanium alloy and the pretreated high entropy alloy self-lubricating composite material;

[0054] The TC4 titanium alloy and the high entropy alloy self-lubricating composite material are placed in a carbon steel sheath, evacuated, and vacuum packaged to obtain a sheath for hot isostatic pressing treatment;

[0055] After the package is sandblasted, it is placed in a hot isostatic pressing device for solid phase diffusion welding treatment (the process is: increase the pressure to 10MPa at room temperature, increase the temperature to 600°C at a heating rate of 20°C / min, keep warm for 10min, continue to increase the pressure to 40MPa, increase the temperature to 800°C at a heating rate of 10°C / min for the second time, keep at the current pressure and temperature for 20min, increase the pressure to 100MPa, and after holding the pressure, increase the temperature to 1050°C at a heating rate of 10°C / min for the third time, keep warm and pressurize for 6h, and air cool), and then use machining to take out the composite block in the package, grind the cross section, observe the interface, and the observation results are as follows: Figure 1 As shown by Figure 1 It can be seen that the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material is well bonded, and an obvious transition layer can be seen to be generated, and the transition layer is 2.5 μm thick;

[0056] The fiber hardness test was performed on the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material, wherein the side hardness of the high entropy alloy self-lubricating composite material was 412 HV, the hardness of the transition layer was 378 HV, and the side hardness of the TC4 titanium alloy was 310 HV;

[0057] The friction and wear test was carried out at room temperature to analyze the friction and wear behavior of the material. The side friction coefficient of the high entropy alloy self-lubricating composite material was 0.35, and the wear rate was 3.3×10 -5 mm / (N·m).

[0058] Example 2

[0059] 85 parts by weight of high entropy alloy powder (the composition of the high entropy alloy is CoCrNiFe, and the particle size is 20 μm), 5 parts by weight of aluminum powder (the particle size is 30 μm) and 10 parts by weight of silver powder (the particle size is 15 μm) are ball-milled and mixed until they are uniformly mixed, and then spark plasma sintered in a graphite mold (the process of spark plasma sintering is: under a pressure of 30 MPa, the temperature is increased from room temperature to 950° C. at a heating rate of 10° C. / min, and molded for 20 minutes), then cooled to room temperature, and demolded to obtain a high entropy alloy self-lubricating composite material;

[0060] Grinding and polishing the TC4 titanium alloy and the high entropy alloy self-lubricating composite material respectively to obtain the pretreated TC4 titanium alloy and the pretreated high entropy alloy self-lubricating composite material;

[0061] The TC4 titanium alloy and the high entropy alloy self-lubricating composite material are placed in a carbon steel sheath, evacuated, and vacuum packaged to obtain a sheath for hot isostatic pressing treatment;

[0062] After the sheath is sandblasted, it is placed in a hot isostatic pressing device for solid phase diffusion welding treatment (the process is: increase the pressure to 10MPa at room temperature, increase to 600°C at a heating rate of 20°C / min, keep warm for 10min, continue to increase the pressure to 40MPa, increase the temperature to 700°C at a heating rate of 10°C / min for the second time, keep at the current pressure and temperature for 30min, increase the pressure to 110MPa, and after holding the pressure, increase the temperature to 1050°C at a heating rate of 10°C / min for three times, keep warm and pressurize for 6h, and air cool), and then the composite block in the sheath is taken out by machining, the cross section is polished, and the interface is observed. The observation result is that the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material is well bonded, and it can be seen that an obvious transition layer is generated, and the transition layer is 3μm thick;

[0063] The fiber hardness test was performed on the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material, wherein the side hardness of the high entropy alloy self-lubricating composite material was 396 HV, the hardness of the transition layer was 368 HV, and the side hardness of the TC4 titanium alloy was 306 HV;

[0064] The friction and wear test was carried out at room temperature to analyze the friction and wear behavior of the material. The side friction coefficient of the high entropy alloy self-lubricating composite material was 0.4, and the wear rate was 3.9×10 -5 mm / (N·m).

[0065] Example 3

[0066] 80 parts by weight of high entropy alloy powder (the composition of the high entropy alloy is CoCrNiFe, and the particle size is 30 μm), 8 parts by weight of aluminum powder (the particle size is 30 μm) and 12 parts by weight of silver powder (the particle size is 20 μm) are ball-milled and mixed until the mixture is uniform, and then spark plasma sintered in a graphite mold (the process of spark plasma sintering is: under a pressure of 30 MPa, the temperature is increased from room temperature to 950° C. at a heating rate of 10° C. / min, and molded for 20 minutes), then cooled to room temperature, and demolded to obtain a high entropy alloy self-lubricating composite material;

[0067] Grinding and polishing the TC4 titanium alloy and the high entropy alloy self-lubricating composite material respectively to obtain the pretreated TC4 titanium alloy and the pretreated high entropy alloy self-lubricating composite material;

[0068] The TC4 titanium alloy and the high entropy alloy self-lubricating composite material are placed in a carbon steel sheath, evacuated, and vacuum packaged to obtain a sheath for hot isostatic pressing treatment;

[0069] After the sheath is sandblasted, it is placed in a hot isostatic pressing device for solid phase diffusion welding treatment (the process is: increase the pressure to 10MPa at room temperature, increase to 600°C at a heating rate of 20°C / min, keep warm for 10min, continue to increase the pressure to 40MPa, increase the temperature to 800°C at a heating rate of 10°C / min for the second time, keep at the current pressure and temperature for 30min, increase the pressure to 110MPa, and after holding the pressure, increase the temperature to 1100°C at a heating rate of 10°C / min for three times, keep warm and pressurize for 6h, and air cool), and then the composite block in the sheath is taken out by machining, the cross section is polished, and the interface is observed. The observation results show that the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material (HEA / TC4 self-lubricating composite material) is well bonded, and it can be seen that an obvious transition layer is generated, and the transition layer is 2.8μm thick;

[0070] The fiber hardness test was performed on the welding interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material, wherein the side hardness of the high entropy alloy self-lubricating composite material was 420 HV, the hardness of the transition layer was 398 HV, and the side hardness of the TC4 titanium alloy was 311 HV;

[0071] The friction and wear test was carried out at room temperature to analyze the friction and wear behavior of the material. The side friction coefficient of the high entropy alloy self-lubricating composite material was 0.35, and the wear rate was 3.0×10 -5 mm / (N·m).

[0072] Comparative Example 1

[0073] TC4 titanium alloy was used as a comparative example;

[0074] The TC4 titanium alloy was subjected to room temperature friction and wear tests to analyze the friction and wear behavior of the material. The friction coefficient was 0.7 and the wear rate was 9.1×10 -3 mm / (N·m).

[0075] Comparative Example 2

[0076] 80 parts by weight of high entropy alloy powder (the composition of the high entropy alloy is CoCrNiFe, and the particle size is 30 μm), 8 parts by weight of aluminum powder (the particle size is 20 μm) and 12 parts by weight of silver powder (the particle size is 20 μm) are ball-milled and mixed until they are uniformly mixed, and then spark plasma sintered in a graphite mold (the process of spark plasma sintering is: under a pressure of 30 MPa, the temperature is increased from room temperature to 950° C. at a heating rate of 10° C. / min, and molded for 20 minutes), then cooled to room temperature, and demolded to obtain a high entropy alloy self-lubricating composite material;

[0077] Grinding and polishing the TC4 titanium alloy and the high entropy alloy self-lubricating composite material respectively to obtain the pretreated TC4 titanium alloy and the pretreated high entropy alloy self-lubricating composite material;

[0078] The TC4 titanium alloy and the high entropy alloy self-lubricating composite material are placed in a carbon steel sheath, evacuated, and vacuum packaged to obtain a sheath for hot isostatic pressing treatment;

[0079] After the package is sandblasted, it is placed in a hot isostatic pressing device for solid phase diffusion welding (the process is: increase the pressure to 10MPa at room temperature, increase the temperature to 600°C at a heating rate of 20°C / min, keep warm for 10min, continue to increase the pressure to 40MPa, increase the temperature to 800°C at a heating rate of 10°C / min for the second time, keep at the current pressure and temperature for 30min, increase the pressure to 110MPa, keep warm and pressure for 6h, and air cool), and then use machining to take out the composite block in the package, grind the cross section, observe the interface, and the observation results are as follows: Figure 2 As shown by Figure 2 It can be seen that at the dissimilar connection interface between the TC4 titanium alloy and the high entropy alloy self-lubricating composite material (HEA / TC4 self-lubricating composite material), no obvious transition layer is formed at the interface between the two alloys, and the bonding performance is weak.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high entropy alloy self-lubricating material and a titanium alloy composite component, characterized in that: The following steps are involved: After mixing medium entropy alloy, aluminum and silver, spark plasma sintering is performed to obtain high entropy alloy self-lubricating material; After encapsulating the high entropy alloy self-lubricating material and the titanium alloy, solid phase diffusion welding is performed to obtain the high entropy alloy self-lubricating material and titanium alloy composite component; The process of the solid phase diffusion welding treatment is as follows: raising the pressure to 10MPa at room temperature, raising the temperature to 600~750℃ at a heating rate of 10~30℃ / min, keeping the temperature for 5~15min, and then raising the pressure to 30~40MPa, raising the temperature to 700~900℃ for the second time at a heating rate of 8~10℃ / min, keeping the temperature for 15~30min, raising the pressure to 80~110MPa, and then raising the temperature to 1000~1200℃ for the third time at a heating rate of 8~10℃ / min, keeping the temperature for 3~7h, and air cooling; The medium entropy alloy is a CoCrNiFe-based medium entropy alloy; The titanium alloy is TC4 titanium alloy.

2. The preparation method according to claim 1, characterized in that The mass ratio of the medium-entropy alloy, aluminum and silver is (75-85): (5-15): (5-15).

3. The preparation method according to claim 1, characterized in that: The particle size of the medium entropy alloy is 10-50 μm.

4. The preparation method according to claim 1 or 2, characterized in that: The particle size of the aluminum is 10 to 50 μm; The particle size of the silver is 15-35 μm.

5. The preparation method according to claim 1, characterized in that: The spark plasma sintering process is: under a pressure of 20-40 MPa, heating from room temperature to 700-1000° C. at a heating rate of 8-10° C. / min, and molding for 10-20 minutes.

6. The preparation method according to claim 5, characterized in that: The spark plasma sintering process is: under a pressure of 25-35 MPa, heating the temperature from room temperature to 900-1000° C. at a heating rate of 8-10° C. / min, and molding for 15-20 minutes.

7. The preparation method according to claim 1, characterized in that: The process of the solid phase diffusion welding treatment is: raising the pressure to 10MPa at room temperature, raising the temperature to 600-700°C at a heating rate of 15-25°C / min, keeping the temperature for 8-12min, continuing to raise the pressure to 35-40MPa, raising the temperature to 700-800°C for the second time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 20-30min, raising the pressure to 100-110MPa, raising the temperature to 1050-1100°C for the third time at a heating rate of 8-10°C / min, keeping the temperature and pressure for 5-6h, and air cooling.

8. A high entropy alloy self-lubricating material and titanium alloy composite component prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for diffusion bonding of annular parts of TiAl alloy and Ti2AlNb alloy through hot isostatic pressing

    CN108526676A

  • Manufacturing method of high-entropy alloy base high-temperature solid lubrication composite material

    CN111218603A

  • Method for connecting high-entropy ceramic and metal

    CN113968749A